Genetic test for the personalization of sport training - Naureen, Zakira; Perrone, Marco; Paolacci, Stefano; Maltese, Paolo Enrico; Dhuli, Kristjana; Kurti, Danjela; Dautaj, Astrit; Miotto, Roberta; Casadei, Arianna; Fioretti, Bernard; Beccari, Tommaso; Romeo, Francesco; et al. (Acta Biomedica Atenei Parmensis, 2020)
Genetic variants may contribute to confer elite athlete status. However, this does not mean that a person with favourable genetic traits would become a champion because multiple genetic interactions and epigenetic contributions coupled with confounding environmental factors shape the overall phenotype. This opens up a new area in sports genetics with respect to commercial genetic testing. The analysis of genetic polymorphisms linked to sport performance would provide insights into the potential of becoming an elite endurance or power performer. This mini-review aims to highlight genetic interactions that are associated with performance phenotypes and their potentials to be used as markers for talent identification and trainability.